Exploring and Developing the Workplace Health Culture Scale in Taiwan - Chang, Yao-Tsung; Tsai, Feng-Jen; Kuo, Chien-Chih; Yeh, Ching-Ying; Chen, Ruey-Yu (Frontiers in Public Health, 2020)
Background: The aim of this study was to develop and validate the workplace health culture scale. Methods: This paper collected and re-organized current definitions about health culture from literature and created the domains and items to develop a new tool. Six enterprises and 2,431 participants were recruited from northern Taiwan for validity test. Results: We found the workplace health culture scale had appropriate reliability and validity, including a good model fit for the 25-item scale. Conclusions: Workplace health culture might be an important domain to the work of WHP. More validity and reliability studies about WHCS in wider industries and the correlation between WHCS and other WHP indicators are needed.